Mr. Rytem, An IoT-Based Smart Irrigation System Application Design for Cultivation Engineering of Allium sativum Garlic in Lowland Conditions - Elsa Wulandari; Rosyid Ridlo Al Hakim; Lilis Dwi Saputri; Isna Aulia Syahdiar; Agung Pangestu; Ariep Jaenul (Institut Teknologi Adhi Tama Surabaya, 2021)
Garlic (Allium sativum L.) is one of the kitchen spices with a distinctive aroma and economic value and has the opportunity to be developed because of the many ingredients that are beneficial to health. Garlic can grow in the highlands and lowlands; the altitude is about 200-250 meters above sea level. It was recorded that throughout 2019 in Indonesia, total imports of garlic reached a value of USD 529.9 million or around 465,344 tonnes. The import value is still high enough to allow sustainable agricultural innovation to be carried out independently, because the use of agricultural land is increasingly limited and does not vary, and is also the main problem of sustainable agriculture. Limited land conditions are also one of the factors for decreasing garlic productivity, and the low productivity of garlic is also caused by the application of cultivation techniques that are not suitable for agricultural land conditions and the surrounding climate because garlic is more often planted in upland conditions. This study provides a smart irrigation system management design which is named “Mr. Rytem” which is integrated between sensors in agricultural land and automation by IoT. The design of